2012
DOI: 10.1111/j.1538-4632.2012.00838.x
|View full text |Cite
|
Sign up to set email alerts
|

Route Choice in Hilly Terrain

Abstract: The orienteering route choice problem involves finding the fastest route between two given points, with running speed determined by various properties of the terrain. In this study, I consider only the effect of climbing or descending on running speed. If a runner's pace p (the reciprocal of speed) varies linearly with gradient m, the straight‐line route always is fastest. However, a nonlinear formulation for p(m), with d2p/dm2 > 0, will more accurately model runners’ capabilities. As a result, critical gradie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 17 publications
(62 reference statements)
0
15
0
2
Order By: Relevance
“…These pace functions may be valid for the elite runners who achieve record times; for any other runner, we might expect the pace function to be a constant multiple of that for elite runners, but only if running performance at all gradients is purely a function of metabolism. In this case, route choice decisions of the sort examined by Kay (2012a) would be identical for all runners. However, by comparing results of physiological experiments on mountain runners on an inclined treadmill with data from mountain races, Minetti et al (2002) found that, whereas uphill running pace does appear to depend only on metabolism, downhill pace in races is considerably slower than might be expected purely on the basis of metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…These pace functions may be valid for the elite runners who achieve record times; for any other runner, we might expect the pace function to be a constant multiple of that for elite runners, but only if running performance at all gradients is purely a function of metabolism. In this case, route choice decisions of the sort examined by Kay (2012a) would be identical for all runners. However, by comparing results of physiological experiments on mountain runners on an inclined treadmill with data from mountain races, Minetti et al (2002) found that, whereas uphill running pace does appear to depend only on metabolism, downhill pace in races is considerably slower than might be expected purely on the basis of metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Originally unrelated to these archaeological questions, William Naismith proposed a rule in 1892 that related human walking speed to the slope of the terrain [32], which was refined later by Aitken [33] and Langmuir [34]. This formula is implemented in a cost distance tool in GRASS GIS [35], but this work applies a different formula that was established later.…”
Section: On Site Catchment Analysis Cost Distance Modeling and Slopementioning
confidence: 99%
“…Pace is defined here as time per unit horizontal distance (as shown on a map), and is a more convenient variable for route choice studies than speed. In an earlier study of the route choice problem (Kay, 2012) we proposed several pace functions, derived in a rather ad hoc manner from various data sources including race results. The present work is a more careful statistical study of results from hill races over a wide range of uphill and downhill gradients, with the objective of deriving a pace function p(m) that should at least be valid for a "typical" elite male hill runner.…”
Section: Introductionmentioning
confidence: 99%
“…Second, the formulation of the route choice problem by Kay (2012), based on a continuous representation of space, requires a twice-differentiable pace function (although this would not be necessary for a route choice algorithm such as that of Collischonn and Pilar (2000) which uses a discretisation of space). Third, Kay (2012) reasoned that d 2 p/dm 2 should be non-negative: a route at constant gradient should never be slower than a route with the same distance and total ascent but involving some steeper and some less steep terrain.…”
Section: Introductionmentioning
confidence: 99%